Design, analysis and fabrication of adjustable wrench / Muhammad Amirul Aiman Mohd Faizal - Mohd Faizal, Muhammad Amirul Aiman (2022)
Adjustable wrench is a project implemented to ease maintenance work especially for woman. The existing adjustable wrench act as loosen and tighten nuts and pipe connectors of different sizes. Based on the survey, there are a lot of problems that users have faced while using adjustable wrench. In the production of project design, there are several factors that need to be considered. Among the factors are in terms of material selection, design concept, measurement analysis, engineering drawing, engineering calculation and CAD’s drawing. This project presenting an implement of theoretical and technical skills in design and fabricate the adjustable wrench using recyclable items. By using all the knowledge, this project can reduce the time of use and can lower the risk of being injured while using the product. Gantt chart as guideline for doing this project. The material used for the project are easy to get and affordable. Use of the machine must be in accordance with the SOP and safety set to prevent any accidents while doing this project. Expected result from this project is to hope that this project can achieve the objectives, which can benefit the society and can reduce the injury at home and at work, fulfil, and can overcome the problems that have been stated by respondents